2012
DOI: 10.1080/07421656.2012.680048
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Creative Clay Work for Reducing Negative Mood: A Randomized Controlled Trial

Abstract: Clay work has long been used in art therapy to achieve therapeutic goals. However, little empirical evidence exists to document the efficacy of such work. The present study randomly assigned 102 adult participants to one of four conditions following induction of a negative mood: (a) handling clay with instructions to create a pinch pot, (b) handling clay with instructions to manipulate it freely, (c) handling a soft stress ball with instructions to toss the ball in a structured manner, or (d) handling a soft s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…The hypothesis that the MBAT group would experience greater reductions in perceived levels of stress on Week 10 compared with the NCT group was rejected. Neither group produced a statistically significant decrease from Week 1 to Week 10, but the NCT group condition had near-statistically significant decrease in scores pretest to posttest on Week 10 (p = .071), coinciding with literature that identifies clay work as having stress-relieving benefits (Kimport & Robbins, 2012).…”
Section: Perceptions Of Stresssupporting
confidence: 73%
See 1 more Smart Citation
“…The hypothesis that the MBAT group would experience greater reductions in perceived levels of stress on Week 10 compared with the NCT group was rejected. Neither group produced a statistically significant decrease from Week 1 to Week 10, but the NCT group condition had near-statistically significant decrease in scores pretest to posttest on Week 10 (p = .071), coinciding with literature that identifies clay work as having stress-relieving benefits (Kimport & Robbins, 2012).…”
Section: Perceptions Of Stresssupporting
confidence: 73%
“…Art therapists are trained psychotherapists with more specified training in the therapeutic properties of art materials and creative processes. Art therapy researchers are gaining a better understanding that in addition to the therapist-client relationship and the directives used in session, the art material itself can affect a client down to neurological and physiological levels (Kaimal et al, 2017;Kaimal et al, 2016;Kimport & Robbins, 2012;Kruk, Aravich, Deaver, & deBeus, 2014;Lorenzo de la Peña, 2016;Sandmire, Gorham, Rankin, & Grimm, 2012;Scholt & Gavron, 2011). Findings from previous studies suggest that the material properties of clay complement mindfulness practices, as even brief clay sculpting is associated with increased gamma and theta power, brain waves linked to information-processing and deep meditative states, respectively (Budzynski, 2006;Kruk et al, 2014).…”
Section: Overview Of Intervention Programmentioning
confidence: 99%
“…Hospitals are increasingly using art therapy to enhance wellness, with an "intentional shift from art on the walls to art for healing" (Lane, 2006, p. 71). In one study, clay work reduced negative moods in medical settings (Kimport & Robbins, 2012), and drawings increased children's awareness of their health conditions and their capacity to problem solve and cope with their illnesses (Rollins, 2005). Madden, Mowry, Gao, Cullen, and Foreman (2010) similarly found that drawing activities enhanced communication, understanding of illness, coping, and the emotional expression of children, and parents reported a reduction in children's pain levels and nausea following art interventions in a transfusion room.…”
Section: Medical Art Therapymentioning
confidence: 98%
“…According to Collie, Backos, Malchiodi, and Spiegel (2006), art-making, especially in the context of PTSD and the military, enhances feelings of safety and relaxation, generates positive and more regulated emotions, and promotes relational bonding. Art therapy furthermore can assist in the integration of fragmentary and sensory traumatic memories (Collie et al, 2006;Lobban, 2016;Walker, 2017) and foster reward perception through positive mood (Chilton et al, 2015;Kimport & Robbins, 2012). While research on TBI and art therapy is limited, individual and group art therapy have been found to be effective in helping TBI patients with emotional expression, socialisation, emotional adaptation to mental and physical disabilities, and communication in a creative and nonthreatening way (Barker & Brunk, 1991;Dodd, 1975;Lazarus-Leff, 1998).…”
Section: Art Therapy Treatment For Ptsd and Tbimentioning
confidence: 99%